Effect of dairy breed and peri-natal live weight on; feed intake, live weight gain, feed efficiency and bio-economic viability of a high milk feeding system for rearing bull calves - Sorley, Marion (2020)
An estimated 101, 959 UK dairy bull calves were euthanized in 2016, mainly due to a lack of profitable bull beef schemes, particularly for the smaller Jersey crossbreed calves. This study aimed to compare the performance of Holstein Friesian and Jersey cross Holstein Friesian breeds, by allocating 60 calves into pairs (n=30) at 10 (± 3) d of age, according to breed and initial live weight (ILW) to one of three groups: Holstein Friesian (HF) of higher ILW (50 ± 0.9 kg); Jersey x HF of higher (JxH) ILW (51 ± 0.9 kg) and Jersey x HF of lower (JxL) ILW (44.1 ± 0.8). All calves were offered milk replacer (MR) at ≤ 10 L/d (MR: 150 g FM/L), which was offered via teat buckets twice daily, along with ad libitum access to cereal based starter, straw and water. Calves were all weaned at 12 weeks of age. Dairy breed and ILW had no effect on pre and post-weaning growth rates, total milk and feed efficiency. Pre-weaning starter consumption was lower for JL compared HF and JH. Initial LW, weaning and post weaning LW were greater, while the number of days taken to reach a LW of 120 kg was 7 d less for HF and JxH compared with JxL calves. It was concluded that, in terms of LW at 10 ± 3 d of age, larger (≥ 50 kg) HF and JxH calves were equally viable, while smaller (< 50 kg) JxL calves could potentially be equally viable at a lower purchase price.